Traditional Rituals of Death: Kanjan Serayong Traditional Ritual Procession for Pesaguan Dayak Ethnicity in Natai Panjang Village, Tumbang Titi District - Benedictus Audy Andarto; Imran Imran (International Journal Ethnic, Racial and Cultural Heritage, 2023)
The research aims to explore information about the Kanjan Serayong traditional ritual of death, which has received limited exposure outside the region, as well as to understand the series of processions involved, ranging from the initial to the core and concluding processes of the Kanjan Serayong custom. This traditional ritual of death is unique to the Dayak Pesaguan tribe, where the mourning atmosphere transforms into a joyful one. However, the community tends to perceive the Kanjan Serayong ritual merely as a festive celebration, overlooking its cultural significance. The methods employed in this research include interviews, direct observation, and documentation. The findings reveal that the Kanjan Serayong traditional ritual begins with the core procession, which includes membulah tetaruk, membulah natar, menyimah tihang sandung, mamatik tambarirang, and menumang kepala. The core procession comprises the presentation of palalawat, manungkung garung, ma'alap tulang, memutus bulen, and memasar tambak. The closing procession involves memantang kasau, papalit porang baliung, and pepiring boras, signifying the conclusion of the Kanjan Serayong traditional ritual. Throughout the Kanjan Serayong ritual, it becomes evident that this traditional practice consists of a complex series of rituals that require considerable financial, temporal, and physical investments, thereby making it profoundly sacred to the Dayak Pesaguan community. Kanjan Serayong is also seen as a way to express gratitude and respect towards deceased family members. In this traditional ritual, the strong sense of kinship among the Dayak Pesaguan community, especially in the village of Natai Panjang, is evident as they collectively prepare for the Kanjan Serayong ritual.